2005
DOI: 10.1111/j.1399-0039.2005.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Allelic polymorphism in introns 1 and 2 of the HLA‐DQA1 gene

Abstract: Human leukocyte antigen (HLA) class II antigens are highly polymorphic membrane glycoproteins, encoded by the A and B genes of DR, DQ, and DP. The polymorphism is mainly located in exon 2, with the exception of DQA1. Of the 27 DQA1 alleles presently known, 18 cannot be identified on the basis of exon 2 alone, but need additional information from the other exons. DQA1 has been reported to be the most ancient class II gene. For evolutionary comparison and to assess the degree of polymorphism outside the exons, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…Although intron 2 sequences have been recently reported [16], we found in our population a new, single nucleotide polymorphism to those previously reported by Voorter et al Intron 2 obtained from different DQA1*050101 samples showed a single nucleotide polymorphism (T/G) at position 53. Intron 2 region from 14 additional individuals showing the haplotype DR17-DQA1*050101-DQB1* 0201 were analyzed to characterize the frequency and HLA haplotypic distribution of the T53G polymorphism.…”
Section: Dqa1*06 Alleles Are Very Infrequent In Caucasianscontrasting
confidence: 42%
See 2 more Smart Citations
“…Although intron 2 sequences have been recently reported [16], we found in our population a new, single nucleotide polymorphism to those previously reported by Voorter et al Intron 2 obtained from different DQA1*050101 samples showed a single nucleotide polymorphism (T/G) at position 53. Intron 2 region from 14 additional individuals showing the haplotype DR17-DQA1*050101-DQB1* 0201 were analyzed to characterize the frequency and HLA haplotypic distribution of the T53G polymorphism.…”
Section: Dqa1*06 Alleles Are Very Infrequent In Caucasianscontrasting
confidence: 42%
“…Genbank accession numbers for DQA1 allele-associated introns are indicated in Table 3. DQA1 intron 2 sequences for 15 DQA1 alleles have been previously reported [16]. Intron 3 polymorphism analysis for the most frequent DQA1 alleles was an essential previous objective for the subsequent group-specific amplification primers design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers were initially designed based on the in- 3= sequencing primer CY5 RTCTCAAWCTTACCTTC 3= UT (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) tron sequences of the DQA1‫1050ء‬ and ‫1030ء‬ alleles and used to sequence homozygous cell lines [21]. After elucidation of the 5= UT region and the 5= end of intron 1 the primers for exon 1 were shown to have a mismatch with several alleles.…”
Section: Primer Selectionmentioning
confidence: 99%
“…The amplification primers for exon 2 were designed on the basis of known intron sequences [21]. They were located in conserved regions of intron 1 and 2, with only one nucleotide difference between the different allele groups.…”
Section: Sbt Of Exons 1-4: Strategy and Primersmentioning
confidence: 99%